2022
DOI: 10.1111/geb.13451
|View full text |Cite
|
Sign up to set email alerts
|

Plant–plant interactions determine taxonomic, functional and phylogenetic diversity in severe ecosystems

Abstract: Aim Plant–plant interactions are an important factor in structuring plant biodiversity. However, most studies on the impacts of plant–plant interactions on biodiversity focus on species richness and to a lesser extent on other facets of diversity. When other facets of biodiversity are considered, studies often include a limited set of environmental conditions. We aimed to quantify the impacts of nurse plants on taxonomic, functional and phylogenetic facets of plant biodiversity and how these impacts change acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 118 publications
(168 reference statements)
6
11
0
Order By: Relevance
“…In contrast, the negative impacts of nurse plants on plant biodiversity were observed under severe environmental conditions (i.e., recent abandoned site). Therefore, we strongly confirm that positive impacts of nurse species are significantly associated with environmental or disturbance level considered (Bashirzadeh et al, 2022 ; Soliveres et al, 2015 ). In this regard, our results provide strong empirical support for positive impacts of nurse species to present a wide range of plant species under moderate disturbance conditions in concordance with stress‐gradient hypothesis (Michalet et al, 2006 ), and secondary succession as an important restorative process (Maestre & Cortina, 2004 ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In contrast, the negative impacts of nurse plants on plant biodiversity were observed under severe environmental conditions (i.e., recent abandoned site). Therefore, we strongly confirm that positive impacts of nurse species are significantly associated with environmental or disturbance level considered (Bashirzadeh et al, 2022 ; Soliveres et al, 2015 ). In this regard, our results provide strong empirical support for positive impacts of nurse species to present a wide range of plant species under moderate disturbance conditions in concordance with stress‐gradient hypothesis (Michalet et al, 2006 ), and secondary succession as an important restorative process (Maestre & Cortina, 2004 ).…”
Section: Discussionsupporting
confidence: 84%
“…This result was consistent with the significant effects of Artemisia on plant biodiversity structure, especially on taxonomic diversity (Bahalkeh et al, 2021;Rahmanian et al, 2021)…”
Section: Plant Biodiversity Through the Presence Of Nurse Plants And ...supporting
confidence: 88%
See 1 more Smart Citation
“…The current results suggest that plants can cope well with the impacts of climatic warming in terms of LES theory but only when undergoing moderate climatic stress; the positive effect of the synergistic coordination between the traits is likely to attenuate, collapse, and even reverse under severe climatic harshness [ 40 ]. In addition, the current results from PCA illustrated that AM and MW had a similar pattern affecting the leaf functional traits (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Onoda et al (2004) indicated that PNUE has a negative relationship with SLA [ 39 ]. However, studies concerning the relationships between plant functional traits under diverse climatic warming scenarios are relatively scant, particularly in drylands (e.g., [ 2 , 8 , 40 ]).…”
Section: Introductionmentioning
confidence: 99%